Analysis of performance indicators in terms of healthy city in Khuzestan province city by using data envelopment analysis (DEA) - nafise marsousi; majid akbari; nazanin hajipour; vahid boustan ahmadi (تحقیقات کاربردی علوم جغرافیایی)
According the increasing population, especially the urban population in the world and increasing environmental pollution caused by it, The need for urban planning and management approaches based on indicators such as Healthy Cities approach seems inevitable. The purpose of this paper is to analyze the efficiency and ranking of healthy city indicators through 36 indicators (socioeconomic, health services, environmental and health care). research method applied research is descriptive, analytic and development. To analyze the data from the non-parametric linear programming technique of data envelopment analysis, cross ineffective, models and software Dea slover Shannon entropy is used. The geographic area of this study is Khuzestan province and its statistical population is 22 cities according to the census of 2016. The results of this research show that in terms of relative efficiency of Ahwaz city due to the centrality of the province and the availability of infrastructure and sanitary services with a relatively high distance with the highest performance and high level of performance was in the first rank. And the cities of Dezful, Shosh, Khorramshahr, Shoshtar, Abadan, Masjed Soleyman and Behbahan were selected as semi-efficient cities. Finally, it can be concluded that in terms of having the indicators of the healthy city, most of the cities of the province are Inefficient (64%).